Growth and Production Response of Glutinous Corn (Zea mays L. ceratina) Plant on the Number of Perennial Seeds Planting and Dosage of NPK - Umi Hanik; Al Machfudz WDP (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the interaction between the number of seeds of planting holes and the dose of NPK on the growth and production of sticky corn plants. The research method used factorial RCBD which was carried out in March-May 2018. The first factor was the number of seeds of planting holes consisting of 2 levels: 1 hole and 2 holes and the second factor was the dose of NPK, P1 = dose 50 kg / ha, P2 = dose of 100 kg / ha, and P3 = dose of 150 kg / ha, repeated 3 times so that 18 units of experiment were obtained. The results showed that the growth and production interaction occurred between the treatment of the number of seeds of planting holes and the dose of NPK. The results of the study that the NPK dose was able to increase the diameter of the cob in the B1P3 treatment which is 3.61 cm. Whereas the treatment of the number of planting holes has a significant effect on the diameter of the stem. While the number of seeds for planting holes can increase the number of leaves and dry weight of stover.